1994
DOI: 10.1002/bem.2250150109
|View full text |Cite
|
Sign up to set email alerts
|

A model for characterizing residential ground current and magnetic field fluctuations

Abstract: The current through the residential grounding circuit is an important source for magnetic fields; field variations near the grounding circuit accurately track fluctuations in this ground current. In this paper, a model is presented which permits calculation of the range of these fluctuations. A discrete network model is used to simulate a local distribution system for a single street, and a statistical model to simulate unbalanced currents in the system. Simulations of three-house and ten-house networks show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In addition to the 1,000-Home Study, the relationship between residential magnetic fields and features of the residential and neighborhood grounding systems has been addressed in several other studies, using both measurements and modeling (Kavet et al 2006;Mader et al 1990Mader et al , 1994Zaffanella et al 1997). A more thorough analysis of 333 1,000-Home Study residences, restricted to the two lowest Wertheimer-Leeper wire code categories (see Kheifets et al 1997 for wire code description) to minimize power line effects, reported that in decreasing order, ground current, number of service drops on the transformer serving the residence, residence age, and location (urban, suburban, rural) influenced the residential magnetic field.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the 1,000-Home Study, the relationship between residential magnetic fields and features of the residential and neighborhood grounding systems has been addressed in several other studies, using both measurements and modeling (Kavet et al 2006;Mader et al 1990Mader et al , 1994Zaffanella et al 1997). A more thorough analysis of 333 1,000-Home Study residences, restricted to the two lowest Wertheimer-Leeper wire code categories (see Kheifets et al 1997 for wire code description) to minimize power line effects, reported that in decreasing order, ground current, number of service drops on the transformer serving the residence, residence age, and location (urban, suburban, rural) influenced the residential magnetic field.…”
Section: Discussionmentioning
confidence: 97%
“…The report concluded that net currents from the medium-voltage distribution system are a common source of residential fields and that their contribution can usually be assessed with reasonable accuracy from outside the residence. Mader et al (1994) produced a model for characterising ground current and magnetic field fluctuations within the curtilage of US homes. Ground currents are caused by a non-balanced system arising from the use of appliances within the home.…”
Section: Introductionmentioning
confidence: 99%